ANALISIS TINGKAT KEPUASAN PELANGGAN TERHADAP PELAYANAN CONTACT CENTER PLN 123 MENGGUNAKAN METODE PIECES - Shosa, Andi; Pusparini, Nur Nawaningtyas; Kharisma, Nanda; Samuel, Samuel (LPPM Universitas Putera Batam, 2025)
As the demands for quality service in the digital era increase, strategic companies such as PT. PLN (Persero) utilize Contact Center 123 as the front line of communication with customers. The background of the success of other digital innovations such as the PLN Mobile application which has been proven to significantly increase customer satisfaction, emphasizes the urgency of continuous evaluation of all service channels. This study aims to measure the level of customer satisfaction with the PLN 123 Contact Center service and provide strategic recommendations for improving quality in the future. The method used is a comprehensive analysis with the PIECES framework, which evaluates six dimensions: Performance, Information, Economy, Control, Efficiency, and Service. The results of the study showed very satisfactory system performance, with all dimensions achieving a level of conformity above 90%. The Control aspect obtained the highest score (94.81%), while the Efficiency aspect was recorded as the lowest (90.26%). Although the overall performance was very good, these findings indicate that there is clear room for improvement in the efficiency area to improve the customer experience.